Labeling genetically modified food in India: Economic consequences in four marketing channels - Bansal, Sangeeta; Gruère, Guillaume P. (International Food Policy Research Institute, 2010)
In 2006, India proposed a draft rule requiring the labeling of all genetically modified (GM) foods and products derived thereof. In this paper, we use primary and secondary market data to assess the economic implications of introducing such a mandatory labeling policy for GM food. We focus on four products that would likely be the first affected by such a regulation in India: cottonseed oil, soybean oil, brinjal (eggplant), and rice. We find that GM food labeling would generate a specific market outcome for each of these products. With GM labeling, virtually all cottonseed oil would be labeled as GM, with limited costs for all actors involved, but also limited benefit for consumers. Labeling soybean oil derived from GM crops could affect market shares for edible oils at the benefit of domestic oils, and non-GM soybean oil could appear on the market at a very limited scale. Labeling GM brinjal would be extremely challenging. Assuming it was implemented, some non-GM brinjal would be sold at a premium in high-income retail outlets, while virtually all others would be labeled GM. A similar outcome would occur for rice, with high-quality rice used for both domestic consumption and exports markets certified non-GM and most of the remaining rice labeled as GM. In each of the cases, labeling would generate significant adjustment costs for the industry and large enforcement costs, and consumer benefit would not always be visible and would highly depend on the degree of enforcement. In fact, voluntary labeling could achieve less-distorted results with lower costs and therefore appears to be a superior regulatory solution. Still, provided enforcement is ensured, a well-designed mandatory labeling regulation with limited product coverage, a non-zero labeling threshold, and an informative labeling content would lead to a much better outcome and lower costs in India than the current draft rule, especially if it is accompanied by a large awareness campaign regarding GM food and consumer safety in India.